Comparison of two models of post‐traumatic osteoarthritis; temporal degradation of articular cartilage and menisci. Issue 3 (10th May 2016) - Fischenich, Kristine M.; Button, Keith D.; DeCamp, Charlie; Haut, Roger C.; Donahue, Tammy L. Haut
ABSTRACT: The objective of this study was to compare longitudinal results from two models of combined anterior cruciate ligament (ACL) and meniscal injury. A modified ACL transection (mACLT) model and a traumatic impact (ACLF) model were used to create an ACL rupture and acute meniscal damage in a Flemish Giant animal model. The animals were euthanized at time points of 4, 8, or 12 weeks. The menisci were assessed for equilibrium and instantaneous compressive modulus, as well as glycosaminoglycan (GAG) coverage. The articular cartilage was mechanically assessed for thickness, matrix modulus, fiber modulus, and permeability. Articular cartilage GAG coverage, fissuring, tidemark integrity, and subchondral bone thickness were measured. Both models resulted in damage indicative of osteoarthritis, including decreased meniscal mechanics and GAG coverage, increased permeability and fissuring of articular cartilage, and decreased GAG coverage. The mACLT model had an early and lasting effect on the menisci mechanics and GAG coverage, while cartilage damage was not significantly affected until 12 weeks. The ACLF model resulted in an earlier change of articular cartilage GAG coverage and fissuring in both the 8 and 12 week groups. The menisci were only significantly affected at the 12 week time point in the ACLF model. We concluded the progression of post traumatic osteoarthritis was dependent on injury modality: a point to be considered in future investigations. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:486–495, 2017.